Jamaica : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Basel Core Principles for Effective Banking Supervision, the CPSS Core Principles for Systemically Important Payment Systems, and IMF Monetary and Financial Policy Transparency Codes. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses key findings of the Financial System Stability Assessment on the Basel Core Principles for Effective Banking Supervision, the Committee for Payment and Settlement Systems (CPSS) Core Principles for Systemically Important Payment Systems, and IMF Monetary and Financial Policy Transparency Codes for Jamaica. The assessment reveals that, although the financial system currently appears well capitalized and supervision has been considerably strengthened in recent years, financial institutions operate in a risky macroeconomic environment. Structural priorities are to improve the insolvency and creditor rights regime and introduce a central securities depository for fixed-income securities.